Culture and education in a pragmatic context - Mey, Jacob L. (Cadernos de Linguagem e Sociedade, 2010)
One area where cultures clash is education. Over the years, we have been witness to such movements as ‘English Only’ in the US (originating in California and Florida, but now operating in a number of other states as well), or the acrimonious European disputes over how much of ‘foreign’ culture can be allowed into the school’s environment (head scarves on the playgrounds, religious symbols like crosses worn around the neck, prayer in the classrooms, and not least use of other languages than the ‘official’ one in teaching and socializing). Pragmatics, by placing the emphasis on the users of language in culture, defuses the potentially explosive elements in such clashes by stressing the need to respect the individual’s options in face of the collective cultural pressure. This is especially important in an area such as education, where schools have historically been used to propagate the ‘domestic’ culture over other cultures, the latter being considered as foreign imports. In a pragmatic view of education, teachers and students should be culture sharers, rather than the former considering themselves exclusively as the rightful owners and proprietary protectors of a culture along with its language